Bioactivity-Guided Fractionation of Pine Needle Reveals Catechin as an Anti-hypertension Agent via Inhibiting Angiotensin-Converting Enzyme - Jian He (Nature Portfolio, 2017)
Abstract Hypertension has been recognized as one of the highest risk factors for cardiovascular diseases. Anti-hypertension agent screening and development has been recognized as a pharmaceutical therapy approach for the cardiovascular diseases treatment. Many kinds of traditional Chinese medicines, such as pine needle, have been used for the treatment of hypertension for a long time, but the bioactive ingredients which responsible for their therapeutic effectiveness are remain unclear. Therefore, screening bioactive chemicals in natural sources is still the most straightforward strategy for novel Angiotensin-converting enzyme inhibitor (ACEi)-based anti-hypertension agents discovery. In this study, we demonstrated a bioactivity-guided fractionation strategy for identifying bioactive fractions and chemicals from pine needle based on LC/MS assay as well as elucidating their mechanisms of pharmacological activity. And we found out the compound in pine needle extracts being ACE-inhibitory active is catechin. When ACE activity was assayed in rat tissue membranes, it was observed that catechin demonstrate ACE inhibition in kidney, lung and testes tissue. All these presents catechin in pine needle could be a potential cardiovascular medicine.